Competitive strategies of differentiation and cost minimization - O. Mikhailov (Управление)
The strategies of differentiation and cost minimization are oriented on reception of competitive advances in the broad range of industries/branches, that allows companies to achieve effective exceed in the industry-average indicators. Using the both strategies can bring the synergetic effect in competition of the subjects and objects. These strategies can reinforce each other and the competitive advances of the company. Strategies of cost minimization and differentiation can coexist and compete. Cost leadership strategy focuses on getting advantages by reducing cost below analogies of all competitors. It is unsufficient the single of cost minimization in the international competing, it is necessary the complex and creative decision of the compound problems, associated with differentiation of products and services.Product differentiation is a business strategy, whereby firms attempt to gain a competitive advantage by increasing the perceived value of their products/services relative to perceived value the other products/services firms; with recording dissatisfied inquiring the customers. Especially distinctive characteristics, properties, attributes of products or services can be one or more-the main thing that they were really important, more useful and valuable for buyers. The differentiation can create on the basis the timing of product introduction, product customization, the best joining the product and services or simultaneously combination of these advantages. Product differentiation is ultimately an expression of the creativity of individuals and groups within the firm. It is limited not only by opportunities, than exist, or than can be created, in particular industry, but by the willingness and ability of firms to creatively explore ways to take advantage of those opportunities.The willingness of consumers to pay more suggests, that important perceptual bases of product differentiation exist. Successful implementation of these strategies can increase consumer sensations/perceptions of the greater value of products/ services and contribute to the expansion of their exports and strengthen the competitiveness of the company in the global economy. The ideal strategy-building process is to achieve a high level of commitment of employees and consumers around a high-quality strategy and the best ways to implement it.